The Relationship Between Papaya Consumption During Pregnancy and Smooth Breast Milk Production in Postpartum Mothers in the Work Area of UPT Puskesmas Bontonompo 1, Gowa Regency - Yudiarsi Eppang; Evi Kusmayanti; Astri Yuliandini; Suhartini (Ammar Dharma Foundation, 2024)
Background: Breastfeeding is the best feeding method for infants. The coverage of exclusive breastfeeding in the Upt Puskesmas Bontonompo 1 work area remains below target due to insufficient milk production. Lactagogum, a substance found in papaya, is known to enhance breast milk production.Objective: This study aims to investigate the relationship between papaya fruit consumption during pregnancy and smooth breastfeeding in postpartum mothers in the Upt Puskesmas Bontonompo 1 work area.Research Method: This study is an observational study with a cross-sectional approach. The sample consisted of 48 respondents selected using purposive sampling based on inclusion criteria in the work area of UPT Puskesmas Bontonompo 1, Gowa Regency. Data analysis was conducted using bivariate analysis with the Mann-Whitney test.Results: The Mann-Whitney test results showed a p value 0.000 < 0,05, indicating a significant relationship between papaya fruit consumption during pregnancy and smooth breastfeeding in postpartum mothers.Conclusion: There is a significant relationship between papaya fruit consumption during pregnancy and smooth breastfeeding in postpartum mothers in the Upt Puskesmas Bontonompo 1 work area.